Terra brasiliensis: la región histórica del Norte uruguayo en la segunda mitad del siglo XIX- 1850-1900 - Palermo López, Eduardo Ramón (2018)
This research has as main objective to determine the existence of a historical region in the border North of the Uruguay, whose territorialisation process we began to study it in our master's thesis. Therefore, this work is its continuation in the time frame from 1850 to 1900. We analyze the space that we call "Banda Norte" - formed by the current territories of Rio Grande do Sul, the North of the Negro River and borders with Brazil - describing their processes of territorialization insofar as we analyze the socio-economic and political context in which the same is are reconfigured as a historical region different from other gaps in the Uruguay. It is important to establish the differences with the processes that occur in the South of the country, in the region of influence of Montevideo. For the purpose of determining the historical region, we have carried out a theoretical reflection on the concepts of space, territory, boundaries, borders, demonstrating that it is possible to identify the existence of a historical, yet unknown and denied region as such by the national historiography, whose socio-historical processes are different from the hegemonic national narrative centralized in Montevideo. We consider this, make a consistent contribution to Uruguayan historiography in the middle which we describe a historical region that encompasses such territories of two national States. We began with the demographic and economic presence of the south riograndenses ranchers in a census of 1850 property, we traveled through the regional slave trade (1850-1880), analyzed the treaties of 1851 with the Brazil Empire and its dire consequences in diplomatic and economic terms, Root of which was possible to support a enslavement disguised as legality and admitted by the Uruguayan government in the form of peonage contracts. We discussed the process of orienting the border territories, disagreeing with the concept of unblocking these territories based on the available demographic and economic statistics, as well as reports of social actors operating on the territory such as teachers, inspectors, politicians and government representatives.